2022
DOI: 10.1002/icd.2312
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of Singapore parenting: Culture‐general and culture‐specific functions of parenting styles and practices

Abstract: Cross‐cultural studies on parenting have identified cultural nuances that may impact the form and functions of parenting styles and practices in different contexts. This scoping review is undertaken with the aim of identifying such nuances in an under‐studied culture, as a starting point to understand and compare the forms and functions of parenting in Asia and beyond. A review of 27 studies showed that optimal parenting styles and practices were associated with positive child development outcomes in Singapore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…In addition, this study also aligns with previous studies in raising awareness of considerations of the sociocultural context in which parenting is embedded when studying and interpreting parenting practices, as outlined in the sociocultural-systems model in IPART. The findings in the present study seem to be line with the growing evidence suggesting that parental control may not have the same connotations and undesirable effects on child outcomes in Western contexts (Cheung & Lim, 2022). In the context of Singapore, there is a strong Western influence on parenting beliefs and ideals in Singaporean families, which is superimposed onto an Asian culture and heritage that places acceptance and respect on parental authority where parenting values revolve around strict discipline and control (Cheung & Lim, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, this study also aligns with previous studies in raising awareness of considerations of the sociocultural context in which parenting is embedded when studying and interpreting parenting practices, as outlined in the sociocultural-systems model in IPART. The findings in the present study seem to be line with the growing evidence suggesting that parental control may not have the same connotations and undesirable effects on child outcomes in Western contexts (Cheung & Lim, 2022). In the context of Singapore, there is a strong Western influence on parenting beliefs and ideals in Singaporean families, which is superimposed onto an Asian culture and heritage that places acceptance and respect on parental authority where parenting values revolve around strict discipline and control (Cheung & Lim, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to a majority of literature conducted in Western populations demonstrating negative outcomes associated with overprotection and authoritarian parenting, H. S. Cheung & Lim (2020) suggest that there may be a "positive" connotation of authoritarian parenting in terms of the emotional meaning and intention attributed to parental controlling behaviour. Given that Singapore has a cultural context with an emphasis on the respect for parental authority (H. S. Cheung & Sim, 2017), children may be more understanding about the intentions behind parental criticism, suggesting that the perception and conveying of well-meaning intentions underlying criticism may promote positive outcomes for children (H. S. Cheung & Lim, 2022). As discussed in H. S. Cheung & Lim (2022), there may be benefits of authoritarian parenting for Singaporean children where a study found that adolescents who experienced authoritarian parenting were observed to have better emotion management (Chong & Chan, 2015), which is similar to results reported in studies conducted in China suggesting a positive association between authoritarian parenting with socioemotional adjustment (Y.…”
Section: G3 Perceptions Of G2 Criticismmentioning
confidence: 99%
“…As such, in this study, parenting practices may have affected 3- to 6-year-olds’ motivation to lie rather than just their ability to tell a lie, and the opposing effects of these two mechanisms may have canceled each other out. Second, it is important to note that this study was conducted in Singapore, a city-state in Southeast Asia where parenting practices are influenced by traditional Asian child-rearing values (Cheung & Lim, 2022). As highlighted by Stewart et al (2002), Asian parents typically use parental control as a means of maintaining harmony and this is often viewed as an expression of love and concern for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Singapore provides a unique sociocultural landscape that is at the crossroads of the East and West. Despite being an Asian country with the majority of the population (74.3%) comprised of ethnically Chinese individuals [22], Singapore has been heavily influenced by Western values due to its history as a British colony, rapid globalization since its independence, and use of English as the lingua franca [23]. In Eastern cultural contexts that are increasingly exposed to Western values, parents' socialization goals could transition from focusing on interdependence-oriented values to embodying a combination of such values with more independence-oriented values.…”
Section: Introductionmentioning
confidence: 99%
“…For example, with regards to emotion socialization, parents may aim to foster their child's ability to independently manage their emotions while maintaining interdependence with others [24,25]. Nonetheless, parenting in Singapore has been suggested to have similarities with traditional Chinese parenting as described in previous literature, such that strict parenting could be endorsed as a form of care for the child and hence may not necessarily have negative connotations for children [23,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%